Datasets covering comparison of tablets versus paper-based tests for young children - Hassler Hallstedt, Martin (Uppsala University, 2016)
Tablets can be used to facilitate systematic testing of academic skills. Yet, when using validated paper tests on tablet, comparability between the mediums must be established. In this dataset, comparability between a tablet and a paper version of a basic math skills test (HRT: Heidelberger Rechen Test 1–4) was investigated.

Four of the five samples included in the current study covered a broad spectrum of schools regarding student achievement in mathematics, proportion of non-native students, parental educational levels, and diversity of ethnic background. The fifth sample, the intervention sample in the Apps-project, presented with similar characterstics except on mathematical achievement where they showed lower results.

To examine the test-retest reliability of the tablet versions of HRT and the Math Battery several samples were tested twice on each measure in various contexts. To test the correlation between the paper and tablet version between HRT, the participants were tested on both paper and tablet versions of HRT using a counterbalanced design to avoid potential order effects. This sample is referred to as the Different formats sample. Finally, norms were collected for HRT, the Math Battery and the mathematical word problem-solving measure. This sample (called the Normative sample) was also use to investigate the correlation, or convergent validity, between HRT and Math Battery (third hypothesis).

See article "Tablets instead of paper-based tests for young children? Comparability between paper and tablet versions of the mathematical Heidelberger Rechen Test 1-4" by Hassler Hallstedt (2018) for further information.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för beskrivning av data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Datasets covering comparison of tablets versus paper-based tests for young children
Datasets accompanying the article "Tablets instead of paper-based tests for young children?"
Keywords: young people; ungdomar; school children; elever; psychological development; psykisk utveckling; mathematical problems; matematiska problem; mathematical thinking; matematiskt tänkande; Applied Psychology; Tillämpad psykologi